Bangladesh the mosaic in green. ([Dhaka, Bangladesh] External Publicity Wing, Ministry of Information, 1996)
Pictographic representation of Bangladesh people and history, its flora and fauna, its resources and its ancient and variegated religious and cultural traditions.
Keywords: Bangladesh